Circus Representation in Chapadão do Bugre, by Mario Palmério (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article proposes to reflect on the importance of research sources in performing arts, mainly on circus arts, and, from then on, present and analyze the use of literary sources in representations about circus. For this, it takes a look at the work Chapadão do Bugre, by Mário Palmério, a writer from Minas Gerais, who, in a vast work, portrays life in the corners of Minas Gerais. In his narrative, the author knew how to thematize the arrival of the circus, in a distant town, and thus, through a literary representation, approach themes debated in research on circus history.
Keywords: Circus representation; Circus; Memory